Pengembangan Bahan Ajar Berbasis Bahan Cerita Aku Bisa Mengasihi Orang Lain (Yohanes 12:34-35) Dalam Pembelajaran Pendidikan Agama Kristen Dan Budi Pekerti Kelas III SD Di Kecamatan Sipoholon Kabupaten Tapanuli Utara - Anita Manullang (Publisher STPKat, 2023)
The aim of this research is to develop a product in the form of story-based teaching materials for the subjects of Christian Religious Education and Character Education for class III elementary school and to determine the suitability of the teaching materials developed. The method used is research and development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The data obtained was analyzed descriptively qualitatively and descriptively quantitatively. Based on the results of research at the analysis stage, the overall average result of the 11 PAK teachers' answers was 3.60, which stated that the score was in the